FOLFIRI plus cetuximab versus FOLFIRI plus bevacizumab for metastatic colorectal cancer (FIRE-3): a post-hoc analysis of tumour dynamics in the final RAS wild-type subgroup of this randomised open-label phase 3 trial. Issue 10 (October 2016) - Stintzing, Sebastian; Modest, Dominik P; Rossius, Lisa; Lerch, Markus M; von Weikersthal, Ludwig Fischer; Decker, Thomas; Kiani, Alexander; Vehling-Kaiser, Ursula; Al-Batran, Salah-Eddin; Heintges, Tobias; Lerchenmüller, Christian; Kahl, Christoph; et al.
Summary: Background: FIRE-3 compared first-line 5-fluorouracil, leucovorin, and irinotecan (FOLFIRI) plus cetuximab with FOLFIRI plus bevacizumab in patients with KRAS exon 2 wild-type metastatic colorectal cancer. The same study also reported an exploratory analysis of a subgroup of patients with tumours that were wild-type at other RAS genes ( KRAS and NRAS exons 2–4). We report here efficacy results for the FIRE-3 final RAS ( KRAS/NRAS, exons 2–4) wild-type subgroup. Moreover, new metrics of tumour dynamics were explored during a centralised radiological review to investigate how FOLFIRI plus cetuximab conferred overall survival benefit in the absence of differences in investigator-assessed objective responses and progression-free survival. Methods: FIRE-3 was a randomised phase 3 trial comparing FOLFIRI plus cetuximab with FOLFIRI plus bevacizumab in the first-line treatment of patients with KRAS exon 2 wild-type metastatic colorectal cancer. The primary endpoint of the FIRE-3 study was the proportion of patients achieving an objective response according to Response Evaluation Criteria In Solid Tumors (RECIST) 1.0 in the intention-to-treat population. A centralised radiological review of CT scans was done in a post-hoc analysis to assess objective response according to RECIST 1.1, early tumour shrinkage, depth of response, duration of response, and time to response in the final RAS wild-type subgroup. Comparisons between treatment groups with respect to objective response rate and early tumour shrinkage were made using Fisher's exact test (two-sided), while differences in depth of response were investigated with a two-sided Wilcoxon test. This trial is registered atClinicalTrials.gov, numberNCT00433927 . Findings: In the final RAS wild-type population (n=400), median overall survival was better in the FOLFIRI plus cetuximab group than the FOLFIRI plus bevacizumab group (33·1 months [95% CI 24·5–39·4] vs 25·0 months [23·0–28·1]; hazard ratio 0·70 [0·54–0·90]; p=0·0059), although investigator-assessed objective response and progression-free survival were comparable between treatment groups. Centralised radiological review of CT-assessable patients (n=330) showed that the proportion of patients achieving an objective response (113 of 157, 72·0% [95% CI 64·3–78·8] vs 97 of 173, 56·1% [48·3–63·6]; p=0·0029), frequency of early tumour shrinkage (107 of 157, 68·2% [60·3–75·4] vs 85 of 173, 49·1% [41·5–56·8]; p=0·0005), and median depth of response (–48·9% [–54·3 to −42·0] vs −32·3% [–38·2 to −29·2]; p<0·0001) were significantly better in extended RAS wild-type patients receiving FOLFIRI plus cetuximab versus those receiving FOLFIRI plus bevacizumab. No differences in duration of response and time to response were observed between treatment groups. Interpretation: This analysis provides a new framework that connects alternative metrics of response to overall survival. Superior response-related outcome parameters, such as early tumour shrinkage and depth of response, obtained by centralised radiological review correlated with the overall survival benefit conferred by FOLFIRI plus cetuximab compared with FOLFIRI plus bevacizumab in the extended RAS wild-type subgroup. Funding: Merck KGaA and Pfizer.